If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -8)(x + 9) = 0 Reorder the terms: (-8 + 2x)(x + 9) = 0 Reorder the terms: (-8 + 2x)(9 + x) = 0 Multiply (-8 + 2x) * (9 + x) (-8(9 + x) + 2x * (9 + x)) = 0 ((9 * -8 + x * -8) + 2x * (9 + x)) = 0 ((-72 + -8x) + 2x * (9 + x)) = 0 (-72 + -8x + (9 * 2x + x * 2x)) = 0 (-72 + -8x + (18x + 2x2)) = 0 Combine like terms: -8x + 18x = 10x (-72 + 10x + 2x2) = 0 Solving -72 + 10x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-36 + 5x + x2) = 0 Factor a trinomial. 2((-9 + -1x)(4 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-9, 4}
| 3(x+6A)-4=6x+2 | | (20+2x)-5x=0 | | 3/4×5/2y=11 | | 1/3x9/4x8-3 | | x+(x+47)=112 | | 12y-27=4y+21 | | 37d=5/14 | | 3y+7=112 | | 4+3x+4x+x=28 | | 0.09xX=97.35 | | 6-(-4+9i)-(-1-i)= | | x^2+2y-16=0 | | 2(x-3)+4(2x-2)=4(3-7x) | | 11.65/x=2.33 | | 5/9*99 | | -5x^4+5=0 | | 68x=180 | | 8x-4x=3(5-x) | | 5(h+3)=25 | | ?/4=12.4 | | 4x+48=3x+8 | | 3x^4+4x^2-15=0 | | 2x-11+3x-47=180 | | 2x+11+3x-47=180 | | 27+7x-2=11x+1 | | 6x-5=2+13 | | 2(x+3)=5+3y | | 9y+y=9y-5 | | 8x-40+2x+20=180 | | 5(h-2)=48 | | log(4x+124)=3 | | 0.09xX=145.62 |